Enterprise Architecture Planning as a Marketing Strategy Based on MSME Product Information Systems - Megasari Megasari (Komunitas Dosen Indonesia, 2021)
This research is intended to assist MSME actors in developing information technology which aims to design a marketing information system and inventory management so as to make it easier for MSME actors to monitor MSME marketing activities easily and precisely. In this study, the Enterprise Architecture Planning (EAP) method was chosen because the EAP method has complex components in the design activities of the information system in question. In addition, qualitative research methods are used to inform the facts that occurred by using observations, interviews, and documentation. So that the process and meaning are shown in this study so that the information provided is in accordance with the facts that occurred, while the informants in this study involved the head of the workshop and two of the workshop employees. Therefore, the selection of this method is considered appropriate to assist MSME actors in planning the development of product marketing information systems by utilizing information technology developments as a step to develop MSMEs that are run. The design of the development of the information system created can be used to make it easier to manage the number of stock items that were previously done manually but with the use of technology it can make it easier for MSMEs to find out the total number of goods automatically correctly based on data recorded by the system and then displayed as the right information. and accurate.